PERBANKAN SYARIAH DI INDONESIA DAN PERAN PERGURUAN TINGGI DALAM RANGKA AKSELERASI - Euis Amalia (University of Merdeka Malang, 2010)
Recently, the shares of sharia banking were too small compared to the asset ofnational banking. The support from the government indicated that new industries were wellconsidered in the national economic development. Various barriers and challenges neededto be solved through total supports from the stakeholders and all elements of society. Highereducation as the center of analysis and research had a strategic role in contributing thoughtsfor product development, supply of human resource, socialization, education and advocationto the implementation of regulation so that acceleration program could make shariabanking as a part of economic pillar of nation especially medium, small and micro enterprisesempowerment.